'Well it depends on what you'd call play': Parent Perspectives on Play in Queensland's Preparatory Year. Issue 2 (June 2016) - Breathnach, Helen; O'Gorman, Lyndal; Danby, Susan
IN THE CONTEXT OF RECENT education reform, Queensland's Preparatory Year (Prep) is undergoing a period of significant change. The framing of Prep under a new national curriculum reflects a shift from its play-based roots to a formalised, subject-based approach. This shift coincides with suggestions that parents may favour more formalised approaches to teaching and learning in the early years. This paper reports on two studies in which parents were interviewed about their views of play in Prep. Data were analysed thematically, with a focus on themes that parents used to talk about play. While parents broadly valued play, the findings suggest that parent participation greatly influenced their acceptance of play-based learning in the formal learning context of Prep. The findings raise implications for educators in fostering strong parent–teacher partnerships in order to facilitate improved parental understanding and support of play in early childhood programs.